Factors influencing the practice of commercial rice production for food security in Vientiane capital, Laos - Saokhamkeo, Phoukeo; Dokmaithes, Rapee; Chompoo, Jamnian; Kheerajitt, Cherdpong (Asian Journal of Agriculture and Rural Development, 2023)
Rice is viewed as an indicator of food security and poverty reduction, but many rural areas of Laos still face rice insufficiency. Dealing with the problem requires transitioning from traditional farming to commercial production using modern techniques. This study aimed to investigate the factors influencing the adoption of commercial rice production for local food security and poverty reduction. The survey included 70 samples in the Namxouang irrigation development area of Vientiane Capital, Laos, using a questionnaire for secondary and primary data collection. Both descriptive and inferential statistics were employed to describe the collected data and analyze factors influencing commercial rice production. The findings revealed that 65.7%, 18.6%, and 15.7% of the respondents engaged in commercial, semi-commercial, and subsistence rice production, respectively. In addition, it also found that land size, labor costs, and machinery costs each had a significant positive relationship with the practice of commercial rice production at a statistical significance level of 0.01. At the same time, household size, media perception, and annual income had significant negative relationships with the practice of commercial rice production at significance levels of 0.01 and 0.05. Therefore, high-quality rice varieties, new rice production techniques, and rice production groups are needed to support farmers using the same technical practices to obtain similar yields. Moreover, regulations are required to control chemical use and manage paddy land. These changes would help achieve the government policy to promote smart farming and good agricultural practice for food security and poverty reduction.